1985
DOI: 10.2165/00007256-198502010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia as an Indicator of Exercise Stress Implications of Recent Findings to Sports Medicine

Abstract: The role of ammonia in exercise-induced fatigue is reviewed. Implications for integrated activity of developing hyperammoneic states, caused by various precipitating conditions such as exercise, liver dysfunction, hypoxia, hyperoxia, and chemical poisoning are described. The central role of ammonia in diverse important metabolic pathways indicates its ubiquitous role in a spectrum of activity ranging from elite exhaustive performance of sportsmen and -women to life-threatening organ dysfunction. The action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
6

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 64 publications
0
10
0
6
Order By: Relevance
“…This increasing ammonia concentration in blood starts to affect the liver and brain, generating fatigue due to excess cerebral ammonia and the inability of peripheral organs to detoxify ammonia. According to Banister et al (1985) and Bianchi et al (1997), hyperammonemia reduces ATP resynthesis, with a consequent increase in the activity of the purine nucleotide cycle (deamination of AMP into IMP). However, deamination of BCAA, and the consequent oxidation of their carbon skeletons for ATP synthesis, occurs due to depletion of muscle and hepatic glycogen stores when fatigue is probably already installed (Jakeman, 1998;Wagenmakers, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This increasing ammonia concentration in blood starts to affect the liver and brain, generating fatigue due to excess cerebral ammonia and the inability of peripheral organs to detoxify ammonia. According to Banister et al (1985) and Bianchi et al (1997), hyperammonemia reduces ATP resynthesis, with a consequent increase in the activity of the purine nucleotide cycle (deamination of AMP into IMP). However, deamination of BCAA, and the consequent oxidation of their carbon skeletons for ATP synthesis, occurs due to depletion of muscle and hepatic glycogen stores when fatigue is probably already installed (Jakeman, 1998;Wagenmakers, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific site of fatigue within active skeletal muscle during submaximal dynamic contractions is unclear in light of a recent investigation by Kayser et al (1993), who observed no evidence of local muscle fatigue during exercise in conditions of severe hypoxia, and suggested that limitations to performance were likely to be central. Furthermore, much attention has been focused on the possible effects of hypoxia-induced hyperammonia on central mechanisms (Bannister et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Plasm a am m onia values, re¯ecting adenosine m onophosphate (AM P) deam ination, m easured in the 8´50 yard test, m ay provide fur ther inform ation regarding the m echanism s responsible for the im provem ents in perform ance observed in the creatine group during the later repetitions (Banister et al, 1985;Greenhaþ et al, 1993b). This reaction is accelerated in extrem e, highintensity exercise bouts (such as in this study) to support high AT P turnover rates.…”
mentioning
confidence: 99%